Overlapping morphological and functional properties between M4 and M5 intrinsically photosensitive retinal ganglion cells - Sonoda, Takuma (J Comp Neurol, 2019)
Multiple retinal ganglion cell (RGC) types in the mouse retina mediate pattern vision by responding to specific features of the visual scene. The M4 and M5 melanopsin-expressing, intrinsically photosensitive retinal ganglion cell (ipRGC) subtypes are two RGC types that are thought to play major roles in pattern vision. The M4 ipRGCs overlap in population with ON-alpha RGCs, while M5 ipRGCs were recently reported to exhibit opponent responses to different wavelengths of light (color opponency). Despite their seemingly distinct roles in visual processing, previous reports have suggested that these two populations may exhibit overlap in their morphological and functional properties, which calls into question whether these are in fact distinct RGC types. Here, we show that M4 and M5 ipRGCs are distinct morphological classes of ipRGCs, but that they cannot be exclusively differentiated based on color opponency and dendritic morphology as previously reported. Instead, we find that M4 and M5 ipRGCs can only be distinguished based on soma size and number of dendritic branch points in combination with SMI-32 immunoreactivity. These results have important implications for clearly defining retinal ganglion cell types and their roles in visual behavior.